Safe lithium battery diaphragm with high heat hole closing function as well as preparation method and application of safe lithium battery diaphragm

By using a multi-layer structural composite membrane and flame retardant coating in the lithium battery separator, and using the combination of bacterial nanocellulose and hot melt materials, the thermal stability and electrolyte absorption problems of the lithium battery separator at high temperatures are solved, and the thermal stability and electrolyte absorption of the lithium battery separator at high temperatures is improved. The safety and energy density of the battery are provided.

CN119231093APending Publication Date: 2024-12-31DONGHUA UNIV

Patent Information

Application Number
CN202411466430.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-13
Filing Date
2024-10-21
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing lithium battery separators have poor thermal stability in high temperature environments, are prone to melting and shrinking, and lead to short-circuit accidents. The low absorption of electrolyte results in large internal resistance of the battery and low energy density.

Method used

Using a multi-layer structural composite membrane, including a bacterial nanocellulose membrane and a composite layer with thermal closure function, it is prepared from hot melt materials and bacterial nanocellulose, combined with a flame retardant coating, optimizes the thermal stability of the membrane and electrolyte absorption. sex.

Benefits of technology

The diaphragm shrinkage is avoided in high temperature environments, the safety and energy density of the battery are improved, the mechanical properties and conductivity of the diaphragm are enhanced, the internal resistance is reduced, and the overall performance of lithium batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231093A_ABST
    Figure CN119231093A_ABST
Patent Text Reader

Abstract

The invention relates to a safe lithium battery diaphragm with a high-heat hole-closing function and a preparation method and application thereof, the lithium battery diaphragm is a composite membrane with a multilayer structure, and comprises a bacterial nano cellulose membrane and a composite layer with the heat hole-closing function; wherein the composite layer is prepared from a hot melting material and bacterial nano cellulose. Compared with a traditional commercial polyolefin diaphragm, the lithium battery diaphragm provided by the invention not only has the characteristics of natural three-dimensional nano network structure, good thermal stability, high liquid absorption rate, high ionic conductivity and the like, but also has thermal closed pores and an optional flame-retardant function, so that the safety of a lithium battery is greatly ensured, and the lithium battery diaphragm has a good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a safe lithium battery diaphragm with high thermal pore closing function, and a preparation method and application thereof. Background Art

[0002] Lithium batteries are mainly composed of positive and negative electrode materials, electrolytes, diaphragms and their shells. As an important component, the diaphragm directly affects key factors such as battery capacity, safety, life and cost. In recent years, the continuous use of lithium batteries in new energy electric vehicles and the safety requirements of their high power output have put forward higher requirements for their diaphragms.

[0003] At present, the lithium battery separators on the market are mainly polyolefin porous membranes, which are mainly made of polyethylene (PE) and polypropylene (PP). Although the separators made of this material have excellent mechanical strength and chemical stability, and self-closed pores at a certain temperature (such as the self-closed pore temperature of PE separators is about 140°C, and the self-closed pore temperature of PP separators is about 160°C), blocking the positive and negative electrodes. However, the membrane still has the following shortcomings: 1) There is internal stress in the preparation process of the separator. In the high-temperature environment generated during high-power discharge, or the stress release in the high-temperature environment when punctured or impacted, the separator will have a significant thermal shrinkage effect, which will cause the positive and negative electrode materials inside the battery to directly contact each other, resulting in internal short circuits, and then fire or explosion and other safety accidents. The melting point of PP is higher than that of PE. During the use of the current commercial PP / PE / PP three-layer separator, when the temperature rises and the PE melts and closes, the outer layer of PP can still maintain good mechanical properties, but if the temperature continues to rise, the PP will melt and cause a short circuit, which will still cause safety accidents. 2) The polarity of polyolefin diaphragm is inconsistent with that of electrolyte, resulting in poor wettability of electrolyte to diaphragm, which makes it impossible for electrolyte to completely infiltrate the internal pores of diaphragm, resulting in high internal resistance of battery, which directly affects the energy density of battery and the migration of lithium ions. 3) The raw materials of polyolefin diaphragm rely on limited fossil energy, but its resources are non-renewable and non-biodegradable, which makes it difficult to meet the requirements of sustainable development strategy, and the production equipment is complicated, which increases the preparation cost of diaphragm. Therefore, it is urgent to develop new thermally stable, thermally closed-cell, high electrolyte absorbency, low-cost and environmentally friendly diaphragm materials.

[0004] Nanocellulose has made breakthrough progress in the field of green energy storage such as fuel cells, supercapacitors, and lithium batteries in recent years due to its fine structure, rich surface active groups, strong mechanical properties, thermal stability, abundant resources and renewable advantages. Among them, bacterial nanocellulose (BNC) is a microbial source nanocellulose, also known as bacterial cellulose (BC), which can be synthesized by bacteria such as Acetobacter, Pseudomonas, Rhizobium, and Achromobacter. It has a natural 3D nanofiber network structure, excellent thermal stability and mechanical properties, high porosity, specific surface area and crystallinity, high biodegradability, and can be fermented using waste crops and wet garbage hydrolyzate. It is green, renewable and has low cost. Therefore, as a new energy material, it has great commercial application prospects.

[0005] In view of the above problems, the invention patent application (publication number CN 112952295 A) coated polyolefin on a plant cellulose-based porous membrane and then prepared a lithium-ion battery separator by multiple extraction methods. However, this method is complicated, the preparation process requires a high temperature, and a pore-forming agent and an extractant need to be added, which not only increases the burden on environmental protection but also has high costs. The prepared separator has low absorption of electrolytes, and the thermal stability of the separator is poor at high temperatures. Therefore, this method does not fundamentally solve the problems of existing separators.

[0006] Therefore, further in-depth research is needed from aspects such as materials and preparation methods to find high-performance lithium battery separators that meet both power and energy storage requirements. Summary of the invention

[0007] The main technical problems to be solved by the present invention are: the existing commercial lithium battery separators 1) have poor thermal stability and will melt and shrink in a high temperature environment, leading to a short circuit accident; 2) the electrolyte has poor wettability on commercial polyolefin separators, and the electrolyte has low absorption in the membrane, resulting in large internal resistance of the battery and low energy density.

[0008] The present invention provides a safe lithium battery separator with high thermal pore-closing function. The lithium battery separator is a multilayer composite membrane, including a bacterial nanocellulose membrane and a composite layer with thermal pore-closing function; wherein the composite layer is prepared from a hot-melt material and bacterial nanocellulose.

[0009] Preferably, the hot-melt material is at least one of polyethylene PE, polypropylene PP, polytetrafluoroethylene PTFE, polyoxymethylene POM, polycarbonate PC, polyamide PA, acrylonitrile-butadiene-styrene ABS, polyphenylene sulfide PPS, polyetheretherketone PEEK, polyethylene terephthalate PET, acrylic plastics, other polyolefins and copolymers thereof.

[0010] Preferably, the mass concentration of the hot-melt material in the composite layer is 0.5%-2%.

[0011] The concentration of the hot melt material directly affects the feasibility of the diaphragm to produce closed pores in a high temperature environment. A low concentration will not produce a thermal closed pore effect. A high concentration will increase the thickness of the diaphragm and increase its internal resistance, while also blocking the pores and weakening its ion transmission performance.

[0012] Preferably, the lithium battery separator is a two-layer structure or a three-layer structure. The two-layer structure is a composite structure of a composite layer with a thermal pore-blocking function and a bacterial nanocellulose membrane; the three-layer structure is a composite structure of a bacterial nanocellulose membrane-a composite layer with a thermal pore-blocking function-a bacterial nanocellulose membrane.

[0013] In the two-layer structure, the bacterial nanocellulose membrane provides a nano-network support skeleton for the hot-melt material, avoiding the thermal shrinkage of the hot-melt material in a high-temperature environment. In the three-layer structure, the bacterial nanocellulose membranes on both sides also provide a nano-network support skeleton, further avoiding the thermal shrinkage of the material. It is worth noting that the three-layer structure also increases the mechanical properties of the diaphragm, playing a key role in preventing dendrite impurities in lithium batteries from piercing and damaging the diaphragm.

[0014] Other functional materials can be added to the above-mentioned safe lithium battery separator with high thermal closure function to make it have composite functions in addition to thermal closure, and the product has great freedom and flexibility in continuous upgrading.

[0015] Furthermore, the lithium battery separator also includes a flame retardant coating.

[0016] Preferably, the flame retardant used in the flame retardant coating is at least one of a bromine-based flame retardant, a phosphorus-based flame retardant, a nitrogen-based flame retardant, an inorganic flame retardant, and a bio-based flame retardant.

[0017] Preferably, the brominated flame retardant includes at least one of decabromodiphenylethane, brominated epoxy resin, and brominated polystyrene; the phosphorus-based flame retardant includes at least one of red phosphorus masterbatch and diphenyl phosphate; the nitrogen-based flame retardant includes at least one of melamine, melamine cyanuric acid, and melamine phosphate; the inorganic flame retardant includes at least one of aluminum hydroxide and magnesium hydroxide; the bio-based flame retardant includes at least one of cardanol, phytic acid, tannic acid, and chitosan.

[0018] Preferably, the mass concentration of the flame retardant in the flame retardant coating is 0.1-1%.

[0019] The concentration of flame retardant will affect the flame retardant effect and ion conductivity of the diaphragm. Low concentration will lead to poor flame retardant effect, and high concentration coating will block pores and cause the ion conductivity of the diaphragm to decrease, which will directly affect the energy density and service life of the lithium battery.

[0020] Preferably, the thickness of the lithium battery separator is 4-35 μm.

[0021] The lithium battery separator that can be prepared by the present invention includes:

[0022] (1) Bacterial nanocellulose lithium battery separator with high thermal closure function: ① Double-layer structure: BPE (BNC-PE), BPP (BNC-PP), BPTFE (BNC-PTFE), BPOM (BNC-POM), BPC (BNC-PC), BPA (BNC-PA), BABS (BNC-ABS), BPPS (BNC-PPS), BPEEK (BNC-PEEK), BPET (BNC-PET), etc.; ② Three-layer structure: BPEB (BNC-PE-BNC), BPPB (BNC-PP-BNC), BPTFEB (BNC-PTFE-BNC), BPOMB (BNC-POM-BNC), BPCB (BNC-PC-BNC), BPAB (BNC-PA-BNC), BABSB (BNC-ABS-BNC), BPPSB (BNC-PPS-BNC), BPEEKB (BNC-PEEK-BNC), BPETB (BNC-PET-BNC), etc.

[0023] (2) Bacterial nanofiber lithium battery separator with high thermal closure and flame retardant function: ① Double-layer structure + flame retardant coating: BPEBr (BPE-bromine flame retardant), BPEP (BPE-phosphorus flame retardant), BPEN (BPE-nitrogen flame retardant), BPEAI (BPE-Al(OH) 3 )、BPEMg(BPE-Mg(OH) 3 )、BPECar(BPE-Car)、BPEPA(BPE-PA)、BPETA(BPE-TA)、BPECS(BPE-CS)、BPPBr(BPP-bromine flame retardant)、BPPP(BPP-phosphorus flame retardant)、BPPN(BPP-nitrogen flame retardant)、BPPAI(BPP-Al(OH) 3 )、BPPMg(BPP-Mg(OH) 3)、BPPCar(BPP-Car)、BPPPA(BPP-PA)、BPPTA(BPP-TA)、BPPCS(BPP-CS)、BPTFEBr(BPTFE-bromine flame retardant)、BPTFEP(BPTFE-phosphorus flame retardant)、BPTFEN(BPTFE-nitrogen flame retardant)、BPTFEAI(BPTFE-Al(OH) 3 )、BPTEMg(BPTFE-Mg(OH) 3 ), BPTFECar (BPTFE-Car), BPTFEPA (BPTFE-PA), BPTFETA (BPTFE-TA), BPTFECS (BPTFE-CS), etc.; ② Three-layer structure + flame retardant coating: BPEBBr (BPEB-bromine flame retardant), BPEBP (BPEB-phosphorus flame retardant), BPEBN (BPEB-nitrogen flame retardant), BPEBAI (BPEB-Al(OH) 3 )、BPEBMg(BPEB-Mg(OH) 3 )、BPEBCar(BPEB-Car)、BPEBPA(BPEB-PA)、BPEBTA(BPEB-TA)、BPEBCS(BPEB-CS)、BPPBBr(BPPB-bromine flame retardant)、BPPBP(BPPB-phosphorus flame retardant)、BPPBN(BPPB-nitrogen flame retardant)、BPPBAI(BPEB-Al(OH) 3 )、BPPBMg(BPPB-Mg(OH) 3 )、BPPBCar(BPPB-Car)、BPPBPA(BPPB-PA)、BPPBTA(BPPB-TA)、BPPBCS(BPPB-CS)、BPTFEBBr(BPTFEB-bromine flame retardant)、BPTFEBP(BPTFEB-phosphorus flame retardant)、BPTFEBN(BPTFEB-nitrogen flame retardant)、BPTFEBAI(BPTFEB-Al(OH) 3 )、BPTFEBMg(BPTFEB-Mg(OH) 3 ), BPTFEBCar (BPTFEB-Car), BPTFEBPA (BPTFEB-PA), BPTFEBTA (BPTFEB-TA), BPTFEBCS (BPTFEB-CS), etc.

[0024] The present invention also provides a method for preparing a safe lithium battery separator with high thermal closure function, comprising the following steps:

[0025] (1) preparing a multilayer composite membrane by static in-situ fermentation, dynamic in-situ horizontal drum fermentation, interfacial in-situ spraying or membrane patching;

[0026] (2) The obtained multilayer composite film is processed by mechanical extrusion and hot pressing and drying to obtain a safe lithium battery separator with high thermal closure function.

[0027] The static in-situ fermentation in step (1) is specifically as follows: an in-situ static method is adopted, and the preparation process is divided into a two-layer structure of pure membrane fermentation and composite layer fermentation with thermal pore closure function, and the three-layer structure is further subjected to pure membrane fermentation on this basis; the pure membrane and the composite layer with thermal pore closure function are fermented for 2-3 days each.

[0028] The dynamic in-situ horizontal drum fermentation in step (1) is specifically as follows: a horizontal drum reactor is used to prepare a composite membrane with a 3D nano-network structure, and the preparation process is divided into a two-layer structure of pure membrane fermentation and composite layer fermentation with thermal pore closure function, and the three-layer structure is further subjected to pure membrane fermentation on this basis; the process parameters of the pure membrane fermentation are: rotation speed 5-8rpm, fermentation time 2-5 days, and the process parameters of the composite layer fermentation with thermal pore closure function are: rotation speed 5-20rpm, fermentation time 2-3 days.

[0029] The interfacial in-situ spraying method in step (1) is specifically as follows: a layer of pure film is first fermented by a static or horizontal dynamic drum method, and at least one of a thermal closed-cell material, a thermal closed-cell material dispersion, or a mixture of a thermal closed-cell material and a culture medium is sprayed thereon to continue fermentation, so as to obtain a two-layer structure with a thermal closed-cell function, and the three-layer structure is then subjected to pure film fermentation on this basis; the pure film and the composite layer with a thermal closed-cell function are each fermented for 2-3 days; the spraying method includes intermittent spraying of equal amounts and continuous spraying of trace amounts.

[0030] The membrane patch in step (1) is specifically: using a purified bacterial nanofiber membrane, hot pressing it with a hot-melt material at a certain temperature to obtain a bacterial nanocellulose-based composite membrane with a thermal closure function. The two-layer structure includes a BNC layer and a hot-melt material layer, and the three-layer structure includes a BNC layer, a hot-melt material layer and a BNC layer. The BNC membrane includes commercially available or prepared by a static / dynamic method, and its wet film thickness is 1-3mm; the hot-melt material can be at least one of particles, fibers, membranes or any form; the hot pressing temperature is the melting temperature of the hot-melt material.

[0031] The preparation method using static and dynamic in-situ fermentation can not only obtain the composite membrane in-situ, but also adjust the thickness of the membrane by changing the culture time. It is worth noting that the dynamic horizontal drum method can further prepare a more uniform composite membrane, further ensuring the thermal closure function of the membrane. At the same time, the BNC-based membrane prepared by this method has a higher porosity and stronger liquid absorption, and its mechanical properties are also better than the composite membrane prepared by static fermentation. It is more noteworthy that the interface in-situ spraying method can further adjust the uniformity of the composite membrane to ensure the functionality of the composite membrane. At the same time, this method can solve the problem of uneven compounding of hot-melt materials with larger particle sizes by the dynamic drum method.

[0032] During the preparation process of step (1), 1 wt% to 5 wt% of a dispersant may be added to help disperse the hot melt material.

[0033] Furthermore, it also includes: immersing the multilayer composite film obtained in step (1) into a solution containing a flame retardant to form a flame retardant coating on its surface; and then treating the obtained multilayer composite film by mechanical extrusion and hot pressing and drying to obtain a safe lithium battery separator with high thermal closure function.

[0034] Preferably, the immersion time in the solution containing the flame retardant is 12-48 hours.

[0035] Preferably, the mechanical extrusion in the above steps is specifically: first extruding at 0.1-0.3 MPa for 5-20 minutes, and then extruding at 0.4-0.6 MPa for 5-20 minutes.

[0036] Preferably, the hot pressing and drying in the above steps is specifically: temperature 70-90° C., time 3-7 days.

[0037] The present invention also provides an application of a safe lithium battery separator with high thermal closure function in a liquid lithium battery, a semi-solid lithium battery or an all-solid lithium battery.

[0038] The principle of the present invention is as follows:

[0039] The bacterial nanocellulose membrane in the present invention has excellent mechanical properties, provides mechanical support for the multilayer composite membrane and the entire diaphragm, and its thermal stability (250°C, almost no shrinkage) also ensures the dimensional stability of the diaphragm under high heat conditions. At the same time, its natural nano-network structure is extremely electrolyte-affinity, and has considerable advantages in ensuring lithium ion transmission and reducing internal resistance. The hot-melt material in the composite layer with thermal pore closure function in the present invention melts under high temperature conditions, blocks the nanopores of BNC, and blocks ion transmission, thereby playing the role of closed pores. Under high heat conditions, the composite layer with thermal pore closure function plays the role of closed pores to prevent short circuits, and the BNC layer provides support for it, ensures the dimensional stability of the diaphragm, avoids short circuits caused by high-temperature diaphragm shrinkage, and effectively avoids a series of safety accidents. Among them, the double-layer BNC in the three-layer structure can provide more excellent mechanical properties for the composite diaphragm, not only can it provide dimensional stability for the diaphragm under high heat conditions, but also has a stronger advantage in preventing dendrites and other impurities inside the battery from penetrating the diaphragm.

[0040] The present invention produces a hot-melt closed-cell effect when the battery is in a high-temperature environment, blocks the positive and negative electrodes, and prevents the battery from thermal runaway and causing dangerous accidents such as deflagration and explosion. At the same time, the melting and closed-cell of the hot-melt material further enhances the mechanical properties of the diaphragm, and also plays an enhancing role in resisting destructive forces such as puncture and impact.

[0041] Beneficial Effects

[0042] (1) Compared with traditional commercial diaphragms, the present invention can produce thermal closure in a high-temperature environment, blocking the contact between the positive and negative electrodes, greatly ensuring the safety of lithium batteries. It can also select suitable hot-melt composite diaphragms according to the use environment of the battery, especially for use in power batteries, which greatly ensures the safety of people's lives.

[0043] (2) Compared with traditional commercial diaphragms, the present invention can also be provided with a flame retardant coating, which can quickly extinguish itself when the battery accidentally burns, and can effectively avoid larger safety accidents.

[0044] (3) Compared with traditional commercial diaphragms, the present invention has better thermal stability, higher specific surface area, liquid absorption performance and ion conductivity. Bacterial nanocellulose and hot-melt materials complement each other. The 3D nanofiber network structure of BNC provides a supporting skeleton, excellent liquid absorption performance and ion transmission performance for the hot-melt material, and the hot-melt material melts in a high temperature environment to further enhance the mechanical properties of the BNC skeleton and has a closed-cell function.

[0045] (4) The thickness of the composite membrane prepared by the dynamic in-situ horizontal drum fermentation, static in-situ fermentation or membrane patch method adopted by the present invention is controllable. The composite membrane is prepared by integrated fermentation, and the preparation method is environmentally friendly and simple. The composite membrane prepared by the dynamic horizontal drum preparation method has the advantages of uniformity, large porosity, and strong mechanical properties.

[0046] (5) The raw materials of the nanofibers used in the present invention are renewable and biodegradable. The raw materials can be fermented from discarded wheat / rice / corn stalks, pulp waste, sugarcane / soybean residues, etc., and the cost is relatively low.

[0047] (6) The preparation method adopted by the present invention is green and environmentally friendly, has a continuous and simple process, a short preparation time, low energy consumption, easy operation, and easy large-scale production.

[0048] (7) The diaphragm of the present invention has good application prospects in the fields of liquid lithium batteries, semi-solid lithium batteries and all-solid lithium batteries, and is of great significance to environmental protection, energy recycling, energy storage, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The surface microstructure SEM images of the BPP composite films with different concentrations prepared in situ in static state in Example 2;

[0050] Figure 2 The figure is a culture medium mixture of PP to which 1% dispersant is added and a culture medium mixture of PP to which no dispersant is added in Example 2;

[0051] Figure 3 These are macroscopic images of the BPP composite membrane with 1% dispersant added and the BPP composite membrane with dispersant added before purification, after purification and after drying in Example 2;

[0052] Figure 4 The transmittance graph of the BPP composite film containing 1% dispersant and the BPP composite film with added dispersant in Example 2 at 0-900nm;

[0053] Figure 5 The transmittance diagram of the BPP composite film containing 1% dispersant and the BPP composite film with added dispersant at 900 nm in Example 2;

[0054] Figure 6 is the moisture content of the BPP composite membranes with different concentrations prepared in situ in the static state in Example 2;

[0055] Figure 7 The macroscopic morphology of the BPP composite membranes with different concentrations prepared in situ in static state in Example 2;

[0056] Figure 8The cross-sectional microscopic morphology SEM images of the BPP composite films with different concentrations prepared in situ in static state in Example 2;

[0057] Fig. 9 This is a statistical diagram of fiber diameters of the 1% BPP composite membrane prepared statically in situ in Example 2;

[0058] Fig.10 Fourier transform infrared spectra of BPP composite films with different concentrations prepared in situ in static state in Example 2;

[0059] Fig.11 This is a graph showing the electrolyte absorption of BPP composite membranes with different concentrations prepared in situ in the static state in Example 2;

[0060] Fig.12 This is a graph showing the thermal shrinkage of BPP composite films with different concentrations prepared in situ in static state in Example 2;

[0061] Fig.13 The contact angle diagram of deionized water and electrolyte of the BPP composite membrane with different concentrations prepared in situ in the static state in Example 2;

[0062] Fig.14 The AC impedance spectra of the BPP composite films with different concentrations prepared in situ in the static state in Example 2;

[0063] Fig.15 This is a rate performance diagram of the 1% BPP composite film prepared statically in situ in Example 2;

[0064] Fig.16 The Coulomb efficiency diagram of the 1% BPP composite film prepared in situ in static state in Example 2;

[0065] Fig.17 The charge and discharge curves of the 1% BPP composite film prepared in situ at different rates in Example 2;

[0066] Fig.18 The surface and side macroscopic morphology of the 1% BPPB composite membrane prepared in situ in static state in Example 9;

[0067] Fig.19 Fourier transform infrared spectra of BPPB composite films with different concentrations prepared in situ in static state in Example 9;

[0068] Fig. 20 This is a statistical diagram of fiber diameters of the 1% BPPB composite membrane prepared statically in situ in Example 9;

[0069] Fig.21 It is a diagram of the moisture content of the BPPB composite membranes with different concentrations prepared in situ in static state in Example 9;

[0070] Fig. 22This is a diagram of the puncture performance of the BPPB composite membranes with different concentrations prepared in situ in static state in Example 9;

[0071] Fig.23 This is a graph showing the electrolyte absorption of the BPPB composite membranes with different concentrations prepared in situ in the static state in Example 9;

[0072] Fig.24 The cross-sectional microscopic SEM images of the BPPB composite membranes with different concentrations prepared in situ in static state in Example 9;

[0073] Fig.25 This is a graph showing the thermal shrinkage of BPPB composite films with different concentrations prepared in situ in static state in Example 9;

[0074] Fig.26 The contact angle diagram of deionized water and electrolyte of the BPPB composite membrane with different concentrations prepared in situ in the static state in Example 9;

[0075] Fig. 27 The surface microstructure SEM images of the BPPB composite membranes with different concentrations prepared in situ in static state in Example 9;

[0076] Fig.28 The AC impedance diagram of the BPPB composite membranes with different concentrations prepared in situ in static state in Example 9;

[0077] Fig.29 This is a rate performance diagram of the 1% BPPB composite membrane prepared statically in situ in Example 9;

[0078] Fig.30 The Coulomb efficiency diagram of the 1% BPPB composite membrane prepared in situ in static state in Example 9;

[0079] Fig.31 The charge and discharge curves of the 1% BPPB composite film prepared in situ at different rates in Example 9;

[0080] Fig.32 The contact angle diagrams of deionized water and electrolyte of the BPP composite membranes with different concentrations prepared by the dynamic horizontal drum in Example 5;

[0081] Fig.33 The macroscopic morphology of the BPPB composite membranes with different concentrations prepared by the dynamic horizontal drum in Example 12;

[0082] Fig.34 This is a graph showing the thermal shrinkage of BPPB composite films of different concentrations prepared by the dynamic horizontal drum in Example 12;

[0083] Fig.35 The longitudinal tensile stress-strain diagram of the BPPB composite membranes with different concentrations prepared by the dynamic horizontal drum in Example 12;

[0084] Fig.36 1 is a transverse tensile stress-strain diagram of the BPPB composite membranes with different concentrations prepared by the dynamic horizontal drum in Example 12;

[0085] Fig.37 The contact angle diagrams of deionized water and electrolyte of the BPPB composite membranes with different concentrations prepared by the dynamic horizontal drum in Example 12;

[0086] Fig.38 The flame retardant properties of the 1% BPPTA composite film prepared by the dynamic horizontal drum in Example 19;

[0087] Fig.39 The technical roadmap of the BNC-based lithium battery separator with thermal closure function prepared by the present invention. DETAILED DESCRIPTION

[0088] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0089] Example 1

[0090] This embodiment adopts a static in-situ fermentation method to prepare a safe lithium battery separator with a thermal pore-closing function. The specific preparation method is as follows:

[0091] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial species, 300 mL of fermentation medium (50 g / L glucose, C 6 H 12 O 6, AR, Sinopharm Group Reagent Co., Ltd.; 5 g / L tryptone, BR, Sinopharm Group Reagent Co., Ltd.; 3 g / L yeast powder, BR, Sinopharm Group Reagent Co., Ltd., the same as other embodiments) were placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken out from the clean bench into a culture dish and cultured at 30°C for 2 days. Subsequently, 20 mL of polyethylene microparticles (PE, ≤8 μm, Fengtai plasticized, the same in other embodiments) with a mass concentration of 0.5%, 1%, and 2% were added to the culture medium and mixed with a solution (the mixed solution was dispersed for 5-10 minutes using an ultrasonic probe of an ultrasonic crusher before sterilization, and 1 wt% of a surfactant as a dispersant can be added to the solution, such as Tween 20, Tween 80, Tuyile dispersant DS-195, DS-172, DS-194H, a cationic surfactant hexadecyl dimethyl ammonium bromide (CTAB), an anionic surfactant sodium dodecylbenzene sulfonate (SDBS), and a non-ionic surfactant polyethylene glycol octyl phenyl ether (Triton X-100). In this embodiment, a non-ionic surfactant polyethylene glycol octyl phenyl ether (Triton X-100) was selected, and the other embodiments used this method for pretreatment), and static fermentation was performed for 2-3 days to obtain S-0.5% BPE, S-1% BPE, and S-2% BPE composite films with a double-layer structure.

[0092] (2) The BPE composite membranes of different concentrations were placed in a sodium hydroxide (NaOH, analytical grade, Sinopharm Shanghai Chemical Reagent Co., Ltd., the same as in other embodiments) solution for purification, and taken out after treatment at 80° C. for 2-4 h. The BPE composite membranes of different concentrations were obtained after rinsing with deionized water until neutral. The purpose of this step was to remove bacterial proteins and residual culture medium adhering to the cellulose membrane to ensure the high purity of bacterial nanocellulose.

[0093] (3) The BPE composite film was extruded by two mechanical extrusions (0.1-0.3 MPa, 5-20 minutes and 0.4-0.6 MPa, 5-20 minutes, the same as in other embodiments), and then placed in an oven at 80° C. and dried on a clamp for 3-7 days to finally obtain S-0.5% BPE, S-1% BPE, and S-2% BPE separators.

[0094] Example 2

[0095] This embodiment adopts a static in-situ fermentation method to prepare a safe lithium battery separator with a thermal pore-closing function. The specific preparation method is as follows:

[0096] (1) Using Komagataeibacter xylinus ATCC 23767 as the strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from the clean bench and placed in a culture dish, and cultured at 30°C for 2 days. Subsequently, 20 mL of polypropylene microparticles (Polyethylene, PP, ≤8 μm, Fengtai plasticized, the same as in other embodiments) with a mass concentration of 0.5%, 1%, and 2% were added to the culture medium and mixed, and static fermentation was performed for 2-3 days to obtain S-0.5% BPP, S-1% BPP, and S-2% BPP composite films with a double-layer structure.

[0097] (2) The BPP composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPP composite membranes of different concentrations.

[0098] (3) The BPP composite film is extruded by two mechanical extrusions, and then placed in an oven at 80° C. and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPP, S-1% BPP, and S-2% BPP separators.

[0099] like Figure 1 Shown are the surface microscopic SEM images of BPP composite membranes with different concentrations prepared in situ statically. It can be seen from the figure that the BPP composite membrane was successfully prepared, and the BNC fibers shuttled through the PP particles, like a net wrapping the PP particles inside.

[0100] Figure 2 The figure shows the culture medium mixture of PP with 1% dispersant added and the culture medium mixture of PP without dispersant added. It can be clearly observed in the figure that after adding the dispersant and sterilizing with high-pressure steam, the PP particles can still be evenly dispersed in the culture medium, while the PP particles without dispersant float above the culture medium. This is because PP is hydrophobic, and adding a dispersant can improve the hydrophobic properties of PP and make it evenly dispersed.

[0101] Figure 3 These are macroscopic pictures of the BPP composite membrane with 1% dispersant added and the BPP composite membrane with dispersant added before purification, after purification and after drying. It can be seen from the pictures that the PP is more evenly dispersed in the BPP composite membrane prepared with the addition of dispersant.

[0102] Figure 4 The transmittance of the BPP composite film with 1% dispersant and the BPP composite film with added dispersant at 0-900nm. It can be seen from the figure that the transmittance of the BPP composite film with added dispersant is stronger, which is because the PP is more evenly dispersed. Figure 5This is a graph of the transmittance of the BPP composite film with 1% dispersant and the BPP composite film with added dispersant at 900nm, which is more able to illustrate the problem. In the graph, the error bar of the BPP composite film with added dispersant is smaller, indicating that the transmittance of each point is more consistent, indicating that it is more uniform.

[0103] Figure 6 The moisture content of BPP composite membranes with different concentrations prepared in situ is shown in the figure. As can be seen from the figure, the moisture content of BPP composite membrane is slightly lower than that of BNC membrane, but still above 90%. This is because the natural 3D nano-network structure of BNC has a high water retention capacity. Its high liquid retention and liquid absorption are obvious advantages as a separator.

[0104] like Figure 7 The macroscopic morphology of the static in-situ prepared BPP composite film with different concentrations, it can be clearly seen in the figure that the PP layer grows on the BNC layer, the color is whitish, and the BNC layer is more transparent, this is because BNC is a 3D nano-network structure, its internal water content is high, and it is transparent. The side view of the composite film also confirms this result, the side shows a double-layer structure, the BNC layer is transparent, and the PP layer is white.

[0105] Figure 8 The cross-sectional microstructure SEM images of the static in-situ prepared BPP composite membranes with different concentrations further confirm that Figure 2 The conclusion drawn in the article is that the BPP composite membrane presents a double-layer structure, including a BNC base layer and a PP layer, and the PP layer is fixed by the BNC fiber mesh. The PP layer is a hot-melt layer, which melts and blocks the mesh of BNC at high temperature, and the BNC base layer provides the membrane with mechanical and thermal stability properties. The two complement each other and are indispensable.

[0106] Fig. 9 This is a statistical diagram of the fiber diameters of static in-situ prepared BPP composite membranes with different concentrations. It can be concluded from the figure that the fiber diameter in the BPP composite membrane is about 90nm.

[0107] Fig.10 The Fourier transform infrared spectra of BPP composite films with different concentrations prepared in situ statically show that a special peak of PP appears in the BPP composite film, which further verifies that PP exists in the BPP composite film.

[0108] Table 1 Thickness, liquid absorption and porosity of BPP composite membranes with different concentrations prepared in situ statically

[0109] sample Film thickness / μm Liquid absorption rate (ethanol) / % Liquid absorption rate (electrolyte) / % Porosity / % Celgard-2500 25 303.06±41.55 356.68±39.67 30.66±2.16 S-BNC-4d 4±0.45 554.63±57.06 680.81±26.49 65.21±2.34 S-0.5%BPP 6±0.68 661.04±76.71 829.77±25.66 68.72±7.91 S-1% BPP 15±1.80 609.37±82.76 632.25±39.40 51.40±1.16 S-2%BPP 15±2.01 476.00±50.30 568.07±34.80 53.70±7.87

[0110] Table 1 shows the thickness, liquid absorption rate (ethanol and electrolyte) and porosity of the BPP composite membranes with different concentrations prepared in situ statically. The liquid absorption rate (ethanol and electrolyte) of the BNC-based membranes in Table 1 is higher than that of the commercial Celgard-2500 membrane; the porosity of the BPP composite membrane decreases with the increase of the PP composite concentration, among which the 0.5% BPP membrane has the largest porosity and the best liquid absorption rate.

[0111] Fig.11 This is a graph of the electrolyte absorption of static in-situ prepared BPP composite membranes with different concentrations. It can be clearly observed in the figure that the commercial Gelgard-2500 membrane has significantly poorer absorption of the electrolyte, while the BNC-based membrane has better absorption of the electrolyte. This result is also verified in Table 1.

[0112] Fig.12 The thermal shrinkage diagram of the static in-situ prepared BPP composite films with different concentrations shows that the commercial Celgard-2500 membrane has an 8% shrinkage rate at 140°C, and its shrinkage rate reaches 62% at 180°C, while the BNC-based membrane has no shrinkage at 180°C, and the BPP composite membrane only slightly curls at 180°C, but does not shrink. This shows that the thermal stability of the BNC-based membrane is relatively excellent.

[0113] Fig.13 The contact angle diagram of deionized water and electrolyte of BPP composite membranes with different concentrations prepared in situ statically. It can be seen from the figure that the commercial 2500 (polypropylene, PP) membrane is hydrophobic and has a lower affinity for electrolyte than the BNC-based membrane. The BNC-based membrane has a very strong lyophilicity. After adding PP, the hydrophilicity and electrolyte affinity of the B surface of the composite membrane are significantly better than those of the pure BNC membrane. This is because the PP in the composite membrane grows inside the BNC, and the thickness of the surface BNC is extremely low, so the liquid (electrolyte and water) will directly penetrate.

[0114] Fig.14 The AC impedance spectra of BPP composite membranes with different concentrations prepared in situ statically show that the impedance of the BPP composite membranes is lower than that of the commercial 2500 membrane, while the impedance of pure BNC is higher than that of the commercial membrane, indicating that the composite structure of the BPP membrane helps to reduce the internal resistance and improve the battery efficiency.

[0115] Fig.15 This is the rate performance diagram of the 1% BPP composite film prepared in situ statically. Fig.16 The Coulomb efficiency diagram is: Fig.17The following are the charge and discharge diagrams at different rates. Compared with commercial diaphragms, the battery prepared with 1% BPP diaphragm has better charge and discharge performance at higher rates, especially at 1C and 2C. The discharge capacity of the battery prepared with 1% BPP diaphragm at 2C is higher than 95mAh / g; the coulomb efficiency of the battery prepared with 1% BPP diaphragm is more stable than that of commercial diaphragm, and is maintained at about 99%; the charge and discharge curves of the battery prepared with 1% BPP diaphragm show that the battery shows a significant stable charge and discharge platform at each rate from 0.1-2C to 0.1C.

[0116] Table 2 shows the elongation at break, tensile strength and Young's modulus of BPP composite films of different concentrations prepared statically in situ. It can be seen from the table that the Young's modulus of the BNC-based diaphragm is much higher than that of the commercial diaphragm. The difference in tensile strength between the transverse and longitudinal directions of the commercial diaphragm is large, and it is more prone to thermal shrinkage and safety accidents in high temperature environments.

[0117] Table 2 Elongation at break, tensile strength and Young's modulus of BPP composite films with different concentrations prepared in situ

[0118] sample Elongation at break (%) Tensile strength(Mpa) Young's modulus(Mpa) S-BNC-4d 8.8±2.6 288.9±63.2 3677.7±938.3 Celgard-2500-horizontal 41.2±16.5 13.5±0.89 154.2±23.4 Celgard-2500-Vertical 39.4±10.1 113.2±7.6 232.1±31.3 0.5% BPP 4.9±2.0 39.0±7.9 1089.2±127.3 1% BPP 7.4±2.4 63.7±4.6 871.9±267.0 2% BPP 7.2±2.8 32.3±2.4 500.6±152.4

[0119] Example 3

[0120] This embodiment adopts a static in-situ fermentation method to prepare a safe lithium battery separator with a thermal pore-closing function. The specific preparation method is as follows:

[0121] (1) Using Komagataeibacter xylinus ATCC 23770 as the strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from the clean bench and placed in a culture dish, and cultured at 30°C for 2 days. Subsequently, 20 mL of polytetrafluoroethylene particles (PTFE, ≤8 μm, Fengtai plasticized, the same as in other embodiments) with a mass concentration of 0.5%, 1%, and 2% were added to the culture medium and mixed, and static fermentation was performed for 2-3 days to obtain S-0.5% BPTFE, S-1% BPTFE, and S-2% BPTFE composite membranes with a double-layer structure.

[0122] (2) The BPTFE composite membranes of different concentrations are placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPTFE composite membranes of different concentrations.

[0123] (3) The BPTFE composite membrane is extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPTFE, S-1% BPTFE, and S-2% BPTFE diaphragms.

[0124] Example 4

[0125] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is as follows:

[0126] (1) Komagataeibacter xylinus ATCC 23767 was used as the bacterial strain, and 300 mL of fermentation medium was horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump was used to add a mixed solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PE composite membrane, thereby obtaining a 0.5% BPE, 1% BPE, and 2% BPE composite membrane with a double-layer structure.

[0127] (2) The BPE composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPE composite membranes of different concentrations.

[0128] (3) The BPE composite film is extruded by mechanical extrusion, and then placed in an oven at 80° C. and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPE, D-1% BPE, and D-2% BPE separators.

[0129] Example 5

[0130] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is as follows:

[0131] (1) Komagataeibacter xylinus ATCC 23770 was used as the bacterial strain, and 300 mL of fermentation medium was horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump was added to a mixed solution of polypropylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium, and dynamic horizontal drum fermentation was continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PP composite membrane, and a 0.5% BPP, 1% BPP, and 2% BPP composite membrane with a double-layer structure was obtained.

[0132] (2) The BPP composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPP composite membranes of different concentrations.

[0133] (3) The BPP composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPP, D-1% BPP, and D-2% BPP diaphragms.

[0134] Fig.32 The contact angle diagram of deionized water and electrolyte of BPP composite membranes with different concentrations prepared by dynamic horizontal drum shows that the affinity of BNC base membrane for liquid is significantly better than that of commercial 2300 diaphragm. The BPP composite membrane prepared by dynamic drum has two-sided absorption for liquid (deionized water and electrolyte). The lyophilicity of BPP-A surface (PP layer surface) is lower than that of BNC surface. This is because PP itself is hydrophobic, and its hydrophobicity will increase with the increase of PP concentration.

[0135] Example 6

[0136] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is as follows:

[0137] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial species, and 300 mL of fermentation medium is horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump is used to add polytetrafluoroethylene particles with a mass concentration of 0.5%, 1%, and 2% and a mixed solution of the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PTFE composite membrane, thereby obtaining a 0.5% BPTFE, 1% BPTFE, and 2% BPTFE composite membrane with a double-layer structure.

[0138] (2) The BPTFE composite membranes of different concentrations are placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPTFE composite membranes of different concentrations.

[0139] (3) The BPTFE composite membrane is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPTFE, D-1% BPTFE, and D-2% BPTFE diaphragms.

[0140] Example 7

[0141] This embodiment adopts the membrane patch method to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is:

[0142] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, the fermentation medium is in situ static plate fermented in an ultra-clean workbench for 5-15 days to obtain a BNC membrane. The above BNC membrane is placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0143] (2) The obtained BNC film is placed in an oven at 80° C. and dried under hot pressing for 3-7 days to obtain a BNC film.

[0144] (3) The PP microspheres were melted in a thin steel mold at 170°C for 2-10 min, and then compressed at 5-10 MPa for 10 min. After cooling to room temperature, a PP film was obtained.

[0145] (4) The BNC film obtained in (2) and the PP film obtained in (3) are cut into the same size, overlapped and fixed with a clamp, then heated at 170° C. for 2-10 min, and cooled to obtain a BPP composite film.

[0146] Example 8

[0147] This embodiment adopts a static in-situ fermentation method to prepare a safe lithium battery separator with a thermal pore-closing function. The specific preparation method is as follows:

[0148] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken from the clean bench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the culture medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPEB, S-1% BPEB, and S-2% BPEB composite membranes with a three-layer structure.

[0149] (2) The BPEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPEB composite membranes of different concentrations.

[0150] (3) The BPEB composite film is extruded by two mechanical extrusions, and then placed in an oven at 80° C. and dried on a clamp for 3-7 days to finally obtain S-0.5% BPEB, S-1% BPEB, and S-2% BPEB separators.

[0151] Example 9

[0152] This embodiment adopts a static in-situ fermentation method to prepare a safe lithium battery separator with a thermal pore-closing function. The specific preparation method is as follows:

[0153] (1) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from an ultra-clean workbench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of 0.5%, 1%, and 2% polypropylene microparticles and the medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPPB, S-1% BPPB, and S-2% BPPB composite membranes with a three-layer structure.

[0154] (2) The BPPB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPPB composite membranes of different concentrations.

[0155] (3) The BPPB composite film was extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried on a clamp for 3-7 days to finally obtain S-0.5% BPPB, S-1% BPPB, and S-2% BPPB separators.

[0156] like Fig.18 The surface and side macroscopic morphology of the static in-situ prepared 1% BPPB composite membrane. Compared with the BPP composite membrane, the membrane has a three-layer structure, in which the PP layer is wrapped by the BNC layer, which can be observed from its side view. Fig.19 Its infrared spectrum also confirmed that PP was compounded into BPPB and the BPPB composite film was successfully prepared.

[0157] Table 3 Thickness, liquid absorption and porosity of BPPB composite membranes with different concentrations prepared in situ statically

[0158] sample Film thickness / μm Liquid absorption rate (ethanol) / % Liquid absorption rate (electrolyte) / % Porosity / % Celgard-2500 25 303.06±41.55 356.68±39.67 30.66±2.16 BNC-6d 14±1.25 334.02±61.91 474.62±12.42 50.79±7.11 S-0.5% BPPB 16±1.54 611.87±53.35 711.59±35.63 57.11±4.53 S-1% BPPB 22±1.59 487.32±57.41 621.37±21.24 47.09±5.04 S-2% BPPB 25±1.60 395.75±89.43 555.59±36.50 38.21±2.03

[0159] Table 3 shows the thickness, liquid absorption rate and porosity of the static in-situ prepared BPPB composite membranes with different concentrations. The table shows that the absorption of ethanol and electrolyte by BNC-based membranes is significantly stronger than that of commercial 2500 membranes. This performance is proportional to its porosity. The natural nano-network structure of BNC has a natural advantage in the absorption of electrolyte. Fig.23 This was verified in (Electrolyte Absorption Diagram of BPPB Composite Membranes with Different Concentrations Prepared in Static In-situ). It can be seen from the figure that the electrolyte dropped onto the BPPB composite membrane is rapidly absorbed and no trace of liquid can be seen on the membrane surface.

[0160] Fig. 20 The fiber diameter statistics of the static in-situ prepared 1% BPPB composite membrane show that the fiber diameter of the BPPB membrane is about 75nm.

[0161] Fig.21 The moisture content diagram of the static in-situ prepared BPPB composite membranes with different concentrations can also illustrate that the BNC-based membrane has a natural advantage in liquid retention performance and has a natural advantage as a membrane.

[0162] Fig. 22 The puncture performance diagram of the BPPB composite membranes with different concentrations prepared in situ statically shows that the puncture performance of the BPPB membrane with a concentration of 1% is the best, comparable to the commercial membrane, and has the potential for application. Table 4 shows the elongation at break, tensile strength and Young's modulus of the BPPB composite membranes with different concentrations prepared in situ statically. The table also shows that the Young's modulus of the BNC-based membrane is much higher than that of the commercial 2500 membrane, and because of its three-layer structure, the mechanical properties of the composite membrane are further increased. The tensile strength of the BPPB composite membranes with concentrations of 0.5% and 1% is almost the same as that of the commercial membrane, and because of the particularity of its preparation process, it does not produce the common differences in the transverse and longitudinal mechanical properties of commercial membranes, and has dimensional stability in high temperature environments.

[0163] Fig.24 The cross-sectional microscopic SEM images of the static in-situ prepared BPPB composite membranes with different concentrations show the microscopic cross-sectional structure of the BNC and BPPB composite membranes. It can be clearly seen that PP grows in BNC. As the PP concentration increases, the thickness of the middle layer increases. It can be seen from Table 3 that its thickness also increases accordingly. The structure presents a three-layer structure like a "sandwich". Fig. 27 The surface microstructure SEM images of static in-situ prepared BPPB composite membranes with different concentrations show that the surface of the BPPB membrane is composed of BNC fibers.

[0164] Fig.25This is a graph of the thermal shrinkage of static in-situ prepared BPPB composite films with different concentrations. The graph directly illustrates that the thermal stability of the BNC-based separator (no shrinkage at 180°C) is significantly better than that of the commercial 2500 separator.

[0165] Fig.26 The contact angle diagram of deionized water and electrolyte of static in-situ prepared BPPB composite membranes with different concentrations shows the lyophilicity of BNC-based membranes and BPPB composite membranes, among which the membranes with PP concentrations of 0.5% and 1% have the best liquid absorption.

[0166] Table 4 Elongation at break, tensile strength and Young's modulus of BPPB composite films with different concentrations prepared in situ statically

[0167] sample Elongation at break (%) Tensile strength(Mpa) Young's modulus(Mpa) BNC-6 7.8±1.5 205.7±22.8 2546.2±597.4 2500-Horizontal 41.2±16.5 13.5±0.89 154.2±23.4 2500-Vertical 39.4±10.1 113.2±7.6 232.1±31.3 0.5% BPPB 16.8±8.9 110.5±6.8 1037.2±161.7 1% BPPB 12.7±4.1 96.5±8.2 514.4±178.3 2% BPPB 11.6±3.0 39.0±7.5 434.3±140.3

[0168] Fig.28 This is the AC impedance diagram of static in-situ prepared BPPB composite membranes with different concentrations. It can be clearly observed in the figure that the impedance of the BPPB composite membrane is lower than that of the commercial membrane, among which 0.5% and 1% BPPB have the best performance.

[0169] Fig.29 , 30 3 and 31 are the rate performance, coulomb efficiency and charge-discharge curves of the 1% BPPB composite membrane prepared in situ at different rates. Fig.29 ) It can be clearly seen that the battery prepared with 1% BPPB membrane has a higher discharge capacity at each rate and is more uniform in each cycle. At 2C, the discharge capacity of the battery prepared with 1% BPPB membrane is higher than 100 mAh / g; Fig.30 It can be observed that the Coulombic efficiency of the commercial separator fluctuates greatly at high rates, while that of 1% BPPB is more stable; Fig.31 It can be concluded that the battery prepared with 1% BPPB shows an obvious stable charge and discharge platform at each rate between 0.1-2C and 0.1C, and after 35 charge and discharge cycles at different rates, the battery capacity has almost no loss.

[0170] Example 10

[0171] This embodiment adopts a static in-situ fermentation method to prepare a safe lithium battery separator with a thermal pore-closing function. The specific preparation method is as follows:

[0172] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from an ultra-clean workbench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of polytetrafluoroethylene with a mass concentration of 0.5%, 1%, or 2% and the culture medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPTFEB, S-1% BPTFEB, and S-2% BPTFEB composite membranes with a three-layer structure.

[0173] (2) The BPTFEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPTFEB composite membranes of different concentrations.

[0174] (3) The BPTFEB composite film is extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPTFEB, S-1% BPTFEB, and S-2% BPTFEB diaphragms.

[0175] Embodiment 11

[0176] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is as follows:

[0177] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump is used to add a mixed solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PE composite layer; finally, a peristaltic pump is used to add 100-200 mL of fermentation medium, and the fermentation is carried out at a rotation speed of 5-8 rpm for 2-3 days to obtain a 0.5% BPEB, 1% BPEB, and 2% BPEB composite membrane with a three-layer structure.

[0178] (2) The BPEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPEB composite membranes of different concentrations.

[0179] (3) The BPEB composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPEB, D-1% BPEB, and D-2% BPEB separators.

[0180] Example 12

[0181] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is as follows:

[0182] (1) Komagataeibacter xylinus ATCC 23770 is used as the bacterial strain, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump is used to add a mixed solution of polypropylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PP composite layer; finally, a peristaltic pump is used to add 100-200 mL of fermentation medium, and the fermentation is carried out at a rotation speed of 5-8 rpm for 2-3 days to obtain a 0.5% BPPB, 1% BPPB, and 2% BPPB composite membrane with a three-layer structure.

[0183] (2) The BPPB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPPB composite membranes of different concentrations.

[0184] (3) The BPPB composite film was extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPPB, D-1% BPPB, and D-2% BPPB diaphragms.

[0185] like Fig.33 The macroscopic morphology of BPPB composite membranes of different concentrations prepared by dynamic horizontal drum can be seen from the figure that the dynamic horizontal drum method can "integrate" to prepare BPPB composite membranes with a three-layer structure. After the membrane is freeze-dried, the middle white PP layer can be clearly observed.

[0186] Fig.34 The thermal shrinkage diagram of BPPB composite films with different concentrations prepared by dynamic horizontal drum. The composite films also show the stable thermal properties of BNC-based films.

[0187] Fig.35 and Fig.36These are the longitudinal tensile and transverse tensile stress-strain diagrams of BPPB composite membranes with different concentrations prepared by dynamic horizontal drum. As can be seen from the figure, the longitudinal tensile strength and transverse tensile strength of the commercial 2500 diaphragm are quite different, with a longitudinal tensile strength of about 108MPa, while its transverse strength is only about 13MPa. The longitudinal and transverse tensile strengths of the BPPB composite membranes with PP concentrations of 0.5% and 1% are both optimal, and higher than the commercial 2500 diaphragm, while the tensile strength of 2% BPPB is the lowest, indicating that the mechanical properties of the BPPB composite membrane are mainly determined by the BNC fibers, and too high a PP concentration will lead to poor mechanical properties of the composite membrane.

[0188] Fig.37 The contact angle diagram of deionized water and electrolyte of BPPB composite membranes with different concentrations prepared by dynamic horizontal drum. It can be seen from the figure that the absorption of deionized water and electrolyte by BNC-based membrane is significantly higher than that of commercial 2500 membrane, while the absorption of electrolyte by BPPB membrane is more prominent, and it can be completely absorbed within 30s after contact with electrolyte.

[0189] Table 5 shows the thickness, liquid absorption rate and porosity of BPPB composite membranes with different concentrations prepared by dynamic horizontal drum. The table also reflects the excellent lyophilicity of BNC-based membranes. The absorption of BPPB composite membranes to electrolyte is higher than that to ethanol, and the absorption of 1% BPPB membrane to electrolyte reaches 669%.

[0190] Table 5 Thickness, liquid absorption and porosity of BPPB composite membranes with different concentrations prepared by dynamic horizontal drum

[0191]

[0192]

[0193] Example 13

[0194] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is as follows:

[0195] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a mixed solution of polytetrafluoroethylene with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium is added by a peristaltic pump, and the dynamic horizontal drum fermentation is continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PTFE composite layer; finally, 100-200 mL of fermentation medium is added by a peristaltic pump, and the horizontal drum fermentation is carried out at a rotation speed of 5-8 rpm for 2-3 days to obtain 0.5% BPTFEB, 1% BPTFEB, and 2% BPTFEB composite membranes with a three-layer structure.

[0196] (2) The BPTFEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPTFEB composite membranes of different concentrations.

[0197] (3) The BPTFEB composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPTFEB, D-1% BPTFEB, and D-2% BPTFEB diaphragms.

[0198] Embodiment 14

[0199] This embodiment adopts the membrane patch method to prepare a safe lithium battery separator with thermal pore closure function. The specific preparation method is:

[0200] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, the fermentation medium is in situ static plate fermented in an ultra-clean workbench for 5-15 days to obtain a BNC membrane. The above BNC membrane is placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0201] (2) The obtained BNC film is placed in an oven at 80° C. and dried under hot pressing for 3-7 days to obtain a BNC film.

[0202] (3) The PE microspheres were melted in a thin steel mold at 130°C for 2-10 min, and then compressed at 5-10 MPa for 10 min. After cooling to room temperature, a PE film was obtained.

[0203] (4) The BNC film obtained in (2) and the PE film obtained in (3) were cut into the same size, overlapped in the order of BNC-PE-BNC and fixed with a clamp, then heated at 130° C. for 2-10 min, and cooled to obtain a BPEB composite film.

[0204] Embodiment 15

[0205] This embodiment adopts a static fermentation method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0206] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in a clean bench and cultured at 30°C for 2 days. Subsequently, 20 mL of a solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, or 2% and the culture medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPE, S-1% BPE, and S-2% BPE composite membranes with a double-layer structure.

[0207] (2) The BPE composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPE composite membranes of different concentrations.

[0208] (3) The purified BPE composite membranes of different concentrations were immersed in a solution containing 0.5% tannic acid (TA, ≥98%, Shanghai Yien Chemical Technology Co., Ltd., the same as in other embodiments) for 12-48 hours, and 0.5% BPETA, 1% BPETA, and 2% BPETA composite membranes were obtained by solution self-assembly.

[0209] (4) The BPE composite film was extruded by two mechanical extrusions, and then placed in an oven at 80° C. and dried on a clamp for 3-7 days to finally obtain S-0.5% BPETA, S-1% BPETA, and S-2% BPETA separators.

[0210] Example 16

[0211] This embodiment adopts a static fermentation method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0212] (1) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in a clean bench and cultured at 30°C for 2 days. Subsequently, 20 mL of a mixed solution of polypropylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the culture medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPP, S-1% BPP, and S-2% BPP composite membranes with a double-layer structure.

[0213] (2) The BPP composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPP composite membranes of different concentrations.

[0214] (3) The purified BPP composite membranes of different concentrations were immersed in a solution containing phytic acid (PA, ≥90%, Shanghai MacLean Biochemical Technology Co., Ltd., the same as in other embodiments) with a mass concentration of 0.5% for 12-48 hours, and 0.5% BPPPA, 1% BPPPA, and 2% BPPPA composite membranes were obtained by solution self-assembly.

[0215] (4) The BPP composite film was extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPPPA, S-1% BPPPA, and S-2% BPPPA diaphragms.

[0216] Embodiment 17

[0217] This embodiment adopts a static fermentation method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0218] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in a clean bench and cultured at 30°C for 2 days. Subsequently, 20 mL of a mixed solution of polytetrafluoroethylene particles with a mass concentration of 0.5%, 1%, and 2% and the culture medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPTFE, S-1% BPTFE, and S-2% BPTFE composite membranes with a double-layer structure.

[0219] (2) The BPTFE composite membranes of different concentrations are placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPTFE composite membranes of different concentrations.

[0220] (3) The purified BPTFE composite membranes of different concentrations were immersed in a solution containing 0.5% mass concentration of cardanol (Car, ≥95%, viscosity 40-60, Cardolite Chemical (Zhuhai) Co., Ltd., the same as in other embodiments) for 12-48 hours, and 0.5% BPTFECar, 1% BPTFECar, and 2% BPTFECar composite membranes were obtained by solution self-assembly.

[0221] (4) The PTFE composite membrane is extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPTFECar, S-1% BPTFECar, and S-2% BPTFECar diaphragms.

[0222] Embodiment 18

[0223] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is as follows:

[0224] (1) Komagataeibacter xylinus ATCC 23767 was used as the bacterial strain, and 300 mL of fermentation medium was horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump was used to add a mixed solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PE composite membrane, thereby obtaining a 0.5% BPE, 1% BPE, and 2% BPE composite membrane with a double-layer structure.

[0225] (2) The BPE composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPE composite membranes of different concentrations.

[0226] (3) The purified BPE composite membranes of different concentrations were immersed in a solution containing 0.5% chitosan (deacetylation degree ≥ 95%, viscosity 100-200 mPa.s, Aladdin Reagent (Shanghai) Co., Ltd., the same as other embodiments) for 12-48 h, and 0.5% BPECS, 1% BPECS, and 2% BPECS composite membranes were obtained by solution self-assembly.

[0227] (4) The BPECS composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPECS, D-1% BPECS, and D-2% BPECS diaphragms.

[0228] Embodiment 19

[0229] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is as follows:

[0230] (1) Komagataeibacter xylinus ATCC 23767 was used as the bacterial strain, and 300 mL of fermentation medium was horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump was used to add a mixed solution of polypropylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PP composite membrane, thereby obtaining a 0.5% BPP, 1% BPP, and 2% BPP composite membrane with a double-layer structure.

[0231] (2) The BPP composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPP composite membranes of different concentrations.

[0232] (3) The purified BPP composite membranes of different concentrations were immersed in a tannic acid solution with a mass concentration of 0.5% for 12-48 hours, and 0.5% BPPTA, 1% BPPTA, and 2% BPPTA composite membranes were obtained by solution self-assembly.

[0233] (4) The BPPTA composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPPTA, D-1% BPPTA, and D-2% BPPTA diaphragms.

[0234] Fig.38 The flame retardant properties of the 1% BPPTA composite film prepared by a dynamic horizontal drum. It can be seen from the figure that the TA coating makes the color of the BPPTA composite film light yellow; the BPP diaphragm burns rapidly after ignition and burns completely within 5 seconds, and has no flame retardancy. The 1% BPPTA diaphragm extinguishes rapidly 1 second after ignition, and there is no smoldering phenomenon, and has excellent flame retardant properties.

[0235] Embodiment 20

[0236] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is as follows:

[0237] (1) Komagataeibacter xylinus ATCC 23770 is used as the bacterial strain, and 300 mL of fermentation medium is horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump is used to add a mixed solution of polytetrafluoroethylene particles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PTFE composite membrane, thereby obtaining a 0.5% BPTFE, 1% BPTFE, and 2% BPTFE composite membrane with a double-layer structure.

[0238] (2) The BPTFE composite membranes of different concentrations are placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPTFE composite membranes of different concentrations.

[0239] (3) The purified BPTFE composite membranes of different concentrations were immersed in a phytic acid solution with a mass concentration of 0.5% for 12-48 hours, and 0.5% BPTFEPA, 1% BPTFEPA, and 2% BPTFEPA composite membranes were obtained by solution self-assembly.

[0240] (4) The BPTFEPA composite membrane was extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPTFEPA, D-1% BPTFEPA, and D-2% BPTFEPA membranes.

[0241] Embodiment 21

[0242] This embodiment adopts a static fermentation method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0243] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken from the clean bench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the culture medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPEB, S-1% BPEB, and S-2% BPEB composite membranes with a three-layer structure.

[0244] (2) The BPEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPEB composite membranes of different concentrations.

[0245] (3) The purified BPEB composite membranes of different concentrations were immersed in a tannic acid solution containing 0.5% by mass concentration for 12-48 hours, and 0.5% BPEBTA, 1% BPEBTA, and 2% BPEBTA composite membranes were obtained by solution self-assembly.

[0246] (4) The BPEBTA composite film was extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried on a clamp for 3-7 days to finally obtain S-0.5% BPEBTA, S-1% BPEBTA, and S-2% BPEBTA diaphragms. Example 22

[0247] This embodiment adopts a static fermentation method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0248] (1) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from an ultra-clean workbench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of 0.5%, 1%, and 2% polypropylene microparticles and the medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPPB, S-1% BPPB, and S-2% BPPB composite membranes with a three-layer structure.

[0249] (2) The BPPB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPPB composite membranes of different concentrations.

[0250] (3) The purified BPPB composite membranes of different concentrations were immersed in a chitosan solution containing a mass concentration of 0.5% for 12-48 hours, and 0.5% BPPBCS, 1% BPPBCS, and 2% BPPBCS composite membranes were obtained by solution self-assembly.

[0251] (4) The BPPBTCS composite film was extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried on a clamp for 3-7 days to finally obtain S-0.5% BPPBCS, S-1% BPPBCS, and S-2% BPPBCS diaphragms.

[0252] Embodiment 23

[0253] This embodiment adopts a static fermentation method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0254] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, 300 mL of fermentation medium was placed in a 30° C. constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from an ultra-clean workbench and placed in a culture dish, and cultured at 30° C. for 2 days; then 20 mL of a mixed solution of polytetrafluoroethylene particles with a mass concentration of 0.5%, 1%, and 2% and the culture medium was added, and static fermentation was performed for 2-3 days; finally, 20 mL of fermentation medium was added, and static fermentation was performed for 2-3 days to obtain S-0.5% BPTFEB, S-1% BPTFEB, and S-2% BPTFEB composite membranes with a three-layer structure.

[0255] (2) The BPTFEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPTFEB composite membranes of different concentrations.

[0256] (3) The purified BPTFEB composite membranes of different concentrations were immersed in a chitosan solution containing a mass concentration of 0.5% for 12-48 hours, and 0.5% BPTFEBCS, 1% BPTFEBCS, and 2% BPTFEBCS composite membranes were obtained by solution self-assembly.

[0257] (4) The BPTFEBCS composite film is extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried on a clamp for 3-7 days to finally obtain S-0.5% BPTFEBCS, S-1% BPTFEBCS, and S-2% BPTFEBCS diaphragms.

[0258] Embodiment 24

[0259] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is as follows:

[0260] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a mixed solution of polyethylene with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium is added by a peristaltic pump, and the dynamic horizontal drum fermentation is continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PE composite layer; finally, 100-200 mL of fermentation medium is added by a peristaltic pump, and the horizontal drum fermentation is carried out at a rotation speed of 5-8 rpm for 2-3 days to obtain a 0.5% BPEB, 1% BPEB, and 2% BPEB composite membrane with a three-layer structure.

[0261] (2) The BPEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPEB composite membranes of different concentrations.

[0262] (3) The purified BPEB composite membranes of different concentrations were immersed in a tannic acid solution containing 0.5% by mass concentration for 12-48 hours, and 0.5% BPEBTA, 1% BPEBTA, and 2% BPEBTA composite membranes were obtained by solution self-assembly.

[0263] (4) The BPEBTA composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPEBTA, D-1% BPEBTA, and D-2% BPEBTA separators.

[0264] Embodiment 25

[0265] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is as follows:

[0266] (1) Komagataeibacter xylinus ATCC 23770 is used as the bacterial species, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a peristaltic pump is used to add a mixed solution of polypropylene with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium to continue dynamic horizontal drum fermentation at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PP composite layer; finally, a peristaltic pump is used to add 100-200 mL of fermentation medium, and the fermentation is carried out at a rotation speed of 5-8 rpm for 2-3 days to obtain a 0.5% BPPB, 1% BPPB, and 2% BPPB composite membrane with a three-layer structure.

[0267] (2) The BPPB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPPB composite membranes of different concentrations.

[0268] (3) The purified BPPB composite membranes of different concentrations were immersed in a solution containing 0.5% cardanol by mass concentration for 12-48 hours, and 0.5% BPPBCar, 1% BPPBCar, and 2% BPPBCar composite membranes were obtained by solution self-assembly method.

[0269] (4) The BPPBTA composite film was extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPPBCar, D-1% BPPBCar, and D-2% BPPBCar diaphragms.

[0270] Embodiment 26

[0271] This embodiment adopts the method of dynamic in-situ horizontal drum fermentation to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is as follows:

[0272] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure membrane; then, a mixed solution of polytetrafluoroethylene with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium is added by a peristaltic pump, and the dynamic horizontal drum fermentation is continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PTFE composite layer; finally, 100-200 mL of fermentation medium is added by a peristaltic pump, and the horizontal drum fermentation is carried out at a rotation speed of 5-8 rpm for 2-3 days to obtain 0.5% BPTFEB, 1% BPTFEB, and 2% BPTFEB composite membranes with a three-layer structure.

[0273] (2) The BPTFEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPTFEB composite membranes of different concentrations.

[0274] (3) The purified BPTFEB composite membranes of different concentrations were immersed in a chitosan solution containing a mass concentration of 0.5% for 12-48 hours, and 0.5% BPTFEBCS, 1% BPTFEBCS, and 2% BPTFEBCS composite membranes were obtained by solution self-assembly.

[0275] (4) The BPTFEBCS composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPTFEBCS, D-1% BPTFEBCS, and D-2% BPTFEBCS diaphragms.

[0276] Embodiment 27

[0277] This embodiment adopts the membrane patch method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0278] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, the fermentation medium is in situ static plate fermented in an ultra-clean workbench for 5-15 days to obtain a BNC membrane. The above BNC membrane is placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0279] (2) The obtained BNC film is placed in an oven at 80° C. and dried under hot pressing for 3-7 days to obtain a BNC film.

[0280] (3) The PP microspheres were melted in a thin steel mold at 170°C for 2-10 min, and then compressed at 5-10 MPa for 10 min. After cooling to room temperature, a PP film was obtained.

[0281] (4) The BNC film obtained in (2) and the PP film obtained in (3) are cut into the same size, overlapped and fixed with a clamp, then heated at 170° C. for 2-10 min, and cooled to obtain a BPP composite film.

[0282] (5) The BPP composite membrane obtained in (4) is immersed in a chitosan solution containing a mass concentration of 0.5% for 12-48 hours to obtain a BPPCS composite membrane by a solution self-assembly method, and then placed in an oven at 80°C and dried on a splint for 1-3 days to obtain a BPPCS diaphragm.

[0283] Embodiment 28

[0284] This embodiment adopts the membrane patch method to prepare a safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0285] (1) Using Komagataeibacter xylinus ATCC 23770 as the bacterial strain, the fermentation medium is in situ static plate fermented in an ultra-clean workbench for 5-15 days to obtain a BNC membrane. The above BNC membrane is placed in a sodium hydroxide solution, treated at 80°C for 2-4 hours, then taken out and rinsed with deionized water until neutral to obtain a purified BNC membrane.

[0286] (2) The obtained BNC film is placed in an oven at 80° C. and dried under hot pressing for 3-7 days to obtain a BNC film.

[0287] (3) The PE microspheres were melted in a thin steel mold at 130°C for 2-10 min, and then compressed at 5-10 MPa for 10 min. After cooling to room temperature, a PE film was obtained.

[0288] (4) The BNC film obtained in (2) and the PE film obtained in (3) were cut into the same size, overlapped in the order of BNC-PE-BNC and fixed with a clamp, then heated at 130° C. for 2-10 min, and cooled to obtain a BPEB composite film.

[0289] (5) The BPEB composite membrane obtained in (4) is immersed in a tannic acid solution with a mass concentration of 0.5% for 12-48 hours to obtain a BPEBTA composite membrane by a solution self-assembly method, and then placed in an oven at 80° C. and dried on a plywood hot press for 1-3 days to obtain a BPEBTA separator.

[0290] Embodiment 29

[0291] This embodiment adopts the interface in-situ spraying method to prepare a double-layer safety lithium battery separator with thermal closure, and the specific preparation method is as follows:

[0292] (1) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in a clean bench and cultured at 30°C for 2 days. Subsequently, a mixed solution of polypropylene microparticles and culture medium with a mass concentration of 0.5%, 1%, and 2% was sprayed on the culture dish, and fermented for 2-3 days to obtain S-0.5% BPP, S-1% BPP, and S-2% BPP composite membranes with a double-layer structure.

[0293] (2) The BPP composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPP composite membranes of different concentrations.

[0294] (3) The BPP composite film is extruded by two mechanical extrusions, and then placed in an oven at 80° C. and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPP, S-1% BPP, and S-2% BPP separators.

[0295] Embodiment 30

[0296] This embodiment adopts the interface in-situ spraying method to prepare a double-layer safety lithium battery separator with thermal closure, and the specific preparation method is as follows:

[0297] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is fermented in a clean bench at a rotation speed of 5-8 rpm for 2-5 days to obtain a first layer of pure film; then, a mixed solution of polyethylene microparticles with a mass concentration of 0.5%, 1%, and 2% and the fermentation medium is sprayed, and dynamic horizontal drum fermentation is continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PE composite film, thereby obtaining a 0.5% BPE, 1% BPE, and 2% BPE composite film with a double-layer structure.

[0298] (2) The BPE composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 hours, taken out, and rinsed with deionized water until neutral to obtain BPE composite membranes of different concentrations.

[0299] (3) The BPE composite film is extruded by mechanical extrusion, and then placed in an oven at 80° C. and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPE, D-1% BPE, and D-2% BPE separators.

[0300] Embodiment 31

[0301] This embodiment adopts the interface in-situ spraying method to prepare a three-layer safety lithium battery separator with thermal closure, and the specific preparation method is as follows:

[0302] (1) Using Komagataeibacter xylinus ATCC 23767 as the strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture solution (20 mL) was taken from the clean bench and placed in a culture dish, and cultured at 30°C for 2 days. Subsequently, a mixed solution of polyethylene microparticles and culture medium with a mass concentration of 0.5%, 1%, and 2% was sprayed on the culture dish, and fermented for 2-3 days. Subsequently, 20 mL of fermentation culture solution was added and cultured for 2-3 days to obtain S-0.5% BPEB, S-1% BPEB, and S-2% BPEB composite membranes with a three-layer structure.

[0303] (2) The BPEB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPEB composite membranes of different concentrations.

[0304] (3) The BPEB composite film is extruded by two mechanical extrusions, and then placed in an oven at 80° C. and dried on a clamp for 3-7 days to finally obtain S-0.5% BPEB, S-1% BPEB, and S-2% BPEB separators.

[0305] Embodiment 32

[0306] This embodiment adopts the interface in-situ spraying method to prepare a three-layer safety lithium battery separator with thermal closure, and the specific preparation method is as follows:

[0307] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure film; then, a mixed solution of polypropylene microparticles with a mass concentration of 0.5%, 1%, and 2% and fermentation medium is sprayed, and dynamic horizontal drum fermentation is continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PP composite film; then, the fermentation medium is added again for pure film fermentation for 2-3 days to obtain a 0.5% BPPB, 1% BPPB, and 2% BPPB composite membrane with a three-layer structure.

[0308] (2) The BPPB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPPB composite membranes of different concentrations.

[0309] (3) The BPPB composite film was extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPPB, D-1% BPPB, and D-2% BPPB diaphragms.

[0310] Embodiment 33

[0311] This embodiment adopts the interface in-situ spraying method to prepare a double-layer safe lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0312] (1) Using Komagataeibacter xylinus ATCC 23767 as the bacterial strain, 300 mL of fermentation medium was placed in a 30°C constant temperature incubator for static fermentation for 2-3 days, and the fermentation culture liquid (20 mL) was taken into a culture dish in a clean bench and cultured at 30°C for 2 days. Subsequently, a mixed solution of polypropylene microparticles and culture medium with a mass concentration of 0.5%, 1%, and 2% was sprayed on the culture dish, and fermented for 2-3 days to obtain S-0.5% BPP, S-1% BPP, and S-2% BPP composite membranes with a double-layer structure.

[0313] (2) The BPP composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPP composite membranes of different concentrations.

[0314] (3) The purified BPP composite membranes of different concentrations were immersed in a chitosan solution containing a mass concentration of 0.5% for 12-48 hours, and 0.5% BPPCS, 1% BPPCS, and 2% BPPCS composite membranes were obtained by solution self-assembly.

[0315] (4) The BPPCS composite membrane was extruded by two mechanical extrusions, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain S-0.5% BPPCS, S-1% BPPCS, and S-2% BPPCS diaphragms.

[0316] Embodiment 34

[0317] This embodiment adopts the interface in-situ spraying method to prepare a three-layer safety lithium battery separator with thermal closure and flame retardant functions. The specific preparation method is:

[0318] (1) Komagataeibacter xylinus ATCC 23767 is used as the bacterial strain, and 300 mL of fermentation medium is horizontally drum fermented at a rotation speed of 5-8 rpm in an ultra-clean workbench for 2-5 days to obtain a first layer of pure film; then, a mixed solution of polypropylene microparticles with a mass concentration of 0.5%, 1%, and 2% and fermentation medium is sprayed, and dynamic horizontal drum fermentation is continued at a rotation speed of 5-20 rpm for 2-3 days to form a BNC and PP composite film; then, the fermentation medium is added again for pure film fermentation for 2-3 days to obtain a 0.5% BPPB, 1% BPPB, and 2% BPPB composite membrane with a three-layer structure.

[0319] (2) The BPPB composite membranes of different concentrations were placed in a sodium hydroxide solution, treated at 80° C. for 2-4 h, taken out, and rinsed with deionized water until neutral to obtain BPPB composite membranes of different concentrations.

[0320] (3) The purified BPPB composite membranes of different concentrations were immersed in a tannic acid solution with a mass concentration of 0.5% for 12-48 hours, and 0.5% BPPBTA, 1% BPPBTA, and 2% BPPBTA composite membranes were obtained by solution self-assembly.

[0321] (4) The BPPBTA composite film is extruded by mechanical extrusion, and then placed in an oven at 80°C and dried by hot pressing for 3-7 days to finally obtain D-0.5% BPPBTA, D-1% BPPBTA, and D-2% BPPBTA diaphragms.

[0322] Comparative Example 1

[0323] According to the preparation method of lithium battery separator described in Chinese patent CN 109065813 A:

[0324] (1) Polypropylene fiber (18-38 μm, Taichi Engineering Materials, hereinafter the same) was washed with acetone (CP, ≥99.0%, Sinopharm Chemical Reagent Co., Ltd., hereinafter the same), degreased and dried, and then placed in a 5% acidic potassium permanganate (CP, ≥99.0%, Sinopharm Chemical Reagent Co., Ltd., hereinafter the same) solution and heated in a 70°C water bath for 10 min to obtain hydrophilic polypropylene fiber.

[0325] (2) After 1 kg of hydrophilic polypropylene fiber is swollen with 5 kg of xylene (CP, ≥99.0%, Sinopharm Chemical Reagent Co., Ltd., the same below) and 5 kg of acrylic acid (>97% (GC), Shanghai MacLean Biochemical Technology Co., Ltd., the same below), 0.01 kg of initiator benzoyl peroxide (75%, Shanghai Aladdin Biochemical Technology Co., Ltd., the same below) and 1 kg of modifier calcium carbonate (98%, San Chemical Technology (Shanghai) Co., Ltd., the same below) are added and stirred to obtain modified polypropylene fiber.

[0326] (3) 110 g of wheat straw fiber (~95%, Hefei Qiansheng Biotechnology Co., Ltd., the same below) and 90 g of modified polypropylene fiber were soaked in 5 L of water for 6 h, and the cellulose fiber was pressurized and pulped.

[0327] (4) Add 3 g of dispersant polyacrylamide (molecular weight 2,000,000-14,000,000, Shanghai Bid Pharmaceutical Technology Co., Ltd., the same below) and 10 g of binder polyhexafluoroethylene (97%, Shanghai MacLean Biochemical Technology Co., Ltd., the same below) to the slurry, add water to disperse and mix evenly.

[0328] (5) The slurry obtained in step (4) is dehydrated through a copper mesh, squeezed, and then dried, and hot-pressed at 120° C. for 20 min to obtain a non-woven fabric membrane of polypropylene fibers and cellulose fibers.

[0329] (6) The nonwoven membrane was gradually heated to 160° C. and kept at this temperature for 35 min for heat treatment to obtain a separator with a cross-linked structure.

[0330] The test results of the composite membrane properties are shown in Table 6.

[0331] Comparative Example 2

[0332] According to the preparation method of lithium battery separator described in Chinese patent CN 109400942 A:

[0333] (1) In an ice-water bath, dry nanocellulose fibers (~95%, Hefei Qiansheng Biotechnology Co., Ltd., the same below) were ultrasonically treated in toluene (AR, ≥99.5%, Sinopharm Chemical Reagent Co., Ltd., the same below) for 10 min. Then, acetic acid (99.5%, TCI (Shanghai) Chemical Industry Development Co., Ltd., the same below), perchloric acid (GR, 70.0-72.0%, Sinopharm Chemical Reagent Co., Ltd., the same below), and acetic anhydride (99%, Shanghai McLean Biochemical Technology Co., Ltd., the same below) were added (1 gram of nanocellulose fibers corresponds to 25 ml of toluene, 20 ml of acetic acid, 0.1 ml of perchloric acid, and 7 ml of acetic anhydride), and the reaction was carried out at 50°C and stirred for 3 hours. Then, the reaction was washed three times with ethanol (GC, >99.8%, Shanghai McLean Biochemical Technology Co., Ltd., the same below). The modified nanocellulose fiber solution was placed in a freeze drying oven and freeze-dried to constant weight to obtain a white solid powder, which is the esterified modified nanocellulose fiber.

[0334] (2) 0.8 parts by weight of the esterified nanocellulose fibers were added to 99.2 parts by weight of liquid paraffin (melting point ≥ 65° C., Shanghai Aladdin Biochemical Technology Co., Ltd., the same below), and stirred for 18 hours to obtain a liquid paraffin dispersion of the modified nanocellulose fibers.

[0335] (3) 30 parts by mass of polyethylene are fed into a twin-screw extruder via a feeder, and 70 parts by mass of a modified nanocellulose fiber liquid paraffin dispersion is supplied from the side feeder of the twin-screw extruder, melt-kneading is performed at 180°C, and a molten solution is prepared in a twin-screw extruder. The obtained molten solution is rolled into a melt from a T-die disposed at the front end of the twin-screw extruder, extruded in a sheet form, and the above-mentioned gel-like sheet is immediately pulled out between a cooling roll and a clamping roll whose surface temperatures are maintained at 30°C, and formed into a gel-like sheet with a thickness of 1000 μm. The gel-like sheet is stretched 6 times in the machine direction (MD) at 110°C using a biaxial stretching machine, and then stretched 7 times in the width direction (TD). After the above-mentioned successive stretching is performed, the stretched sheet is immersed in a liquid tank filled with dichloromethane, and the liquid paraffin is dissolved and extracted to obtain a base film without a pore-forming agent, and the base film without a pore-forming agent is dried by a dryer. The obtained dried microporous membrane was stretched by 0.05% in the TD direction using a tenter at an internal temperature of 130°C and heat treated for 2 minutes. Then, the width was reduced by 3.5% in the TD direction by free shrinkage in a heat treatment machine at an internal temperature of 110°C, dried and fixed, and wound up with a winding roller. The desired composite microporous membrane was obtained.

[0336] The test results of the composite membrane properties are shown in Table 6.

[0337] Comparative Example 3

[0338] According to the preparation method of lithium battery separator described in Chinese patent CN 112952295 A:

[0339] (1) paraffin oil and polyethylene were mixed in a mass ratio of m (paraffin oil): m (polyolefin) = 1000:4, heated to 140°C to dissolve, and stirred for 1 hour to make the mixture uniform;

[0340] (2) cooling the solution obtained in step (1) by 120° C., adding n-octane (GC, >99%, Shanghai MacLean Biochemical Technology Co., Ltd., the same below), and stirring evenly;

[0341] (3) coating the mixture obtained in step (2) on a cellulose porous membrane with a thickness of 20 μm, and then placing it in a constant temperature box at 110° C. for 1 hour, taking it out and cooling it at -10° C. to obtain a composite membrane containing paraffin oil and n-octane;

[0342] (4) immersing the composite membrane obtained in step (3) in n-hexane (AR, ≥97.0%, Sinopharm Chemical Reagent Co., Ltd., the same below), extracting n-octane and paraffin oil therein, repeating the extraction 3 times, each extraction for 1 hour, to obtain a composite membrane containing only n-hexane as the solvent;

[0343] (5) The composite membrane obtained in step (4) is placed in a constant temperature oven and baked at 70° C. for 10 h to remove the n-hexane therein, thereby obtaining a polyethylene-cellulose composite membrane.

[0344] The test results of the composite membrane properties are shown in Table 6.

[0345] Comparative Example 4

[0346] According to the preparation method of lithium battery separator described in Chinese patent CN 109585756 A:

[0347] (1) Preparation of spinning solution: After heating the solution, add ultra-high molecular weight polyethylene and bacterial cellulose, heat to 120-150°C, stir and emulsify, then add flame retardant (aluminum hydroxide, 1-3 μm, 99.6%, San Chemical Technology (Shanghai) Co., Ltd., the same below), filler (nano silicon dioxide, 99.5%, 15 nm, Shanghai Bid Pharmaceutical Technology Co., Ltd., the same below) and adjuvant (antioxidant: 99%, Shanghai MacLean Biochemical Technology Co., Ltd.; flow modifier: Shanghai Yien Chemical Technology Co., Ltd.; nucleating agent: Roan's reagent) in sequence, stir and emulsify evenly;

[0348] (2) Preparation of gel spinning: adding the mixture obtained in step (1) into a twin-screw spinning machine, heating to 250-300° C., melting and stirring evenly, spraying the spinning through a spinning assembly, and cooling through circulating water to form gel spinning;

[0349] (3) Stretching and extraction of gel spinning: After the prepared gel spinning is cold stretched, it is extracted under ultrasonic wave, and then dried at low temperature under negative pressure, and the drying temperature is 40-60°C;

[0350] (4) Heat stretching: Heat, maintain the temperature at 100-160°C, stretch 5-8 times, and then roll up for use.

[0351] The test results of the composite membrane properties are shown in Table 6.

[0352] Comparative Example 5

[0353] The commercial separator Celgard-2325 was used as comparative example 5. The performance test results are shown in Table 6.

[0354] Comparative Example 6

[0355] The commercial separator Celgard-2500 was used as comparative example 6. The performance test results are shown in Table 6.

[0356] From Table 6, it can be seen that the absorption performance of BNC-based PP membrane for electrolyte is significantly higher than that of Comparative Examples 1-6, while the absorption performance of Comparative Examples 1-4 for electrolyte is not as high as that of commercial membranes, and is far lower than that of BNC-based membranes for electrolyte; in terms of tensile properties, the tensile strength of statically cultured BNC-based PP composite membranes is lower than that of dynamically cultured, while the tensile properties of composite membranes prepared using cellulose (dynamic BNC-based PP composite membranes and Comparative Examples 1-4) are better than those of commercial membranes; cellulose has naturally stable thermal properties, and the BNC-based PP membrane has almost no shrinkage at 180°C for 30 minutes, while the commercial membrane has a more serious shrinkage, and the membranes prepared by Comparative Examples 1-4 also shrink to varying degrees. This shows that BNC-based PP composite membranes can be used as membrane materials with excellent performance.

[0357] Table 6 Thickness, porosity, liquid absorption, tensile strength and thermal shrinkage of the diaphragms prepared by different methods

[0358]

Claims

1. A safe lithium battery separator with high thermal closure function, characterized in that: The lithium battery separator is a multi-layer composite membrane, including a bacterial nanocellulose membrane and a composite layer with a thermal pore-closing function; wherein the composite layer is prepared from a hot-melt material and bacterial nanocellulose.

2. The safe lithium battery separator according to claim 1, characterized in that: The hot melt material is at least one of polyethylene PE, polypropylene PP, polytetrafluoroethylene PTFE, polyoxymethylene POM, polycarbonate PC, polyamide PA, acrylonitrile-butadiene-styrene ABS, polyphenylene sulfide PPS, polyetheretherketone PEEK, polyethylene terephthalate PET, acrylic plastics, other polyolefins and copolymers thereof.

3. The safe lithium battery separator according to claim 1, characterized in that: The mass concentration of the hot-melt material in the composite layer is 0.5%-2%.

4. The safe lithium battery separator according to claim 1, characterized in that: The lithium battery separator also includes a flame retardant coating.

5. The safe lithium battery separator according to claim 4, characterized in that: The flame retardant used in the flame retardant coating is at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an inorganic flame retardant, and a bio-based flame retardant.

6. The safe lithium battery separator according to claim 5, characterized in that: The bromine-based flame retardant includes at least one of decabromodiphenylethane, brominated epoxy resin, and brominated polystyrene; the phosphorus-based flame retardant includes at least one of red phosphorus masterbatch and diphenyl phosphate; the nitrogen-based flame retardant includes at least one of melamine, melamine cyanuric acid, and melamine phosphate; the inorganic flame retardant includes at least one of aluminum hydroxide and magnesium hydroxide; the bio-based flame retardant includes at least one of cardanol, phytic acid, tannic acid, and chitosan.

7. The safe lithium battery separator according to claim 5, characterized in that: The mass concentration of the flame retardant in the flame retardant coating is 0.1-1%.

8. A method for preparing a safe lithium battery separator with high thermal closure function, comprising the following steps: (1) preparing a multilayer composite membrane by static in-situ fermentation, dynamic in-situ horizontal drum fermentation, interfacial in-situ spraying or membrane patching; (2) The obtained multilayer composite film is processed by mechanical extrusion and hot pressing and drying to obtain a safe lithium battery separator with high thermal closure function.

9. The preparation method according to claim 8, characterized in that: Also includes: Immersing the multilayer composite film obtained in step (1) in a solution containing a flame retardant to form a flame retardant coating on the surface thereof; The obtained multilayer composite film is then processed by mechanical extrusion and hot pressing and drying to obtain a safe lithium battery separator with high thermal closure function.

10. Use of the safe lithium battery separator with high thermal closure function as claimed in claim 1 in liquid lithium batteries, semi-solid lithium batteries or all-solid lithium batteries.

Citation Information

Patent Citations

  • A lithium ion battery diaphragm with a heat closing function, preparation method and application thereof

    CN109065813A

  • Composite micro porous membrane and preparation method thereof

    CN109400942A

  • Lithium battery separator and preparation thereof

    CN109585756A

  • Polyolefin-cellulose composite diaphragm and preparation method thereof

    CN112952295A

  • Lithium battery composite separator having three-dimensional network structure and preparation method of lithium battery composite separator

    CN106299212A

Cited By

  • Separator for lithium secondary battery, and lithium secondary battery comprising same

    WO2026205858A1